2017
DOI: 10.7554/elife.24463
|View full text |Cite|
|
Sign up to set email alerts
|

Proteomic mapping of cytosol-facing outer mitochondrial and ER membranes in living human cells by proximity biotinylation

Abstract: The cytosol-facing membranes of cellular organelles contain proteins that enable signal transduction, regulation of morphology and trafficking, protein import and export, and other specialized processes. Discovery of these proteins by traditional biochemical fractionation can be plagued with contaminants and loss of key components. Using peroxidase-mediated proximity biotinylation, we captured and identified endogenous proteins on the outer mitochondrial membrane (OMM) and endoplasmic reticulum membrane (ERM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
365
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(405 citation statements)
references
References 103 publications
(187 reference statements)
17
365
1
Order By: Relevance
“…A promising strategy to obtain such information in living cells is represented by proximity labeling of cytosol‐facing OMM proteins (see e.g., Ref. ). In this approach a monomeric peroxidase called APEX2 was genetically targeted to OMM.…”
Section: Questions To Be Answered and Future Challengesmentioning
confidence: 99%
“…A promising strategy to obtain such information in living cells is represented by proximity labeling of cytosol‐facing OMM proteins (see e.g., Ref. ). In this approach a monomeric peroxidase called APEX2 was genetically targeted to OMM.…”
Section: Questions To Be Answered and Future Challengesmentioning
confidence: 99%
“…mitochondrial matrix and intermembrane space (Rhee et al 2013;Hung et al 2016)) as well as for local proteomes (e.g. inside cilia (Mick et al 2015), at synaptic clefts , at endoplasmic reticulum-mitochondria contact sites (Cho et al 2017;Hung et al 2017), demonstrate the usefulness and versatility of these techniques. Although the potential utility for PL in plants is equally tremendous, its adaptation in plants is proving challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Two generations of APX engineering, namely APEX and APEX2, have led to successful proximity labeling under the reducing environment in mammalian cells. By fusing to various proteins of interest, APEX2 has opened up avenues for spatially resolved proteomic mapping in live cell sub‐compartments, such as ciliary plasma membrane, mitochondrial matrix, endoplasmic reticulum membrane, and nucleus …”
Section: Introductionmentioning
confidence: 99%
“…By fusing to various proteins of interest, APEX2 has opened up avenues for spatially resolved proteomic mapping in live cell sub-compartments, such as ciliary plasma membrane, mitochondrial matrix, endoplasmic reticulum membrane, and nucleus. [14][15][16][17][18][19] One prerequisite of a good tagging protein is to fold and express well when fusing with a protein of interest. We found that APEX2 fusions, however, often caused dramatically decreased expression in human cells.…”
mentioning
confidence: 99%